207k views
2 votes
I can't solve this :

I can't solve this :-example-1
User JayDeeEss
by
6.1k points

1 Answer

5 votes

Answer:

1. No Solution

2. Infinity solutions

3. One Solution

Explanation:

1. 2x-3=2(x-1)

distribute the 2

2x - 3 = 2x - 2

2x cancels out

-3 ≠ -2

therefore no solution

2. 3(x - 4) = 2x - 9 +x - 3

distribute and add common factors

3x - 12 = 3x - 12

3x cancels out

-12 = -12

Therefore infinity solutions

3. 2(2x + 3) = 2(3x + 2)

distribute

4x + 6 = 6x + 4

minus 6x

-2x + 6 = 4

minus 6

-2x = -2

There for x=1 meaning one solution

User Grant Langseth
by
6.7k points